Sybil Attack Detection Based on Authentication Process Using Digital Security Certificate Procedure for Data Transmission in MANET - Muthusamy, P; Sheela, T (International Journal of Engineering and Technology, 2018)
Mobile devices are becoming very popular due to the wide range of networking competence for the mobile device users. The security issues in MANET become the control towards the management of the multiple numbers of nodes in the MANET is distributed. To strategy for overcome the Sybil attack in MANET and improve the efficiency of the Sybil attack detection by enhancing the data confidentiality and reliability. The primary objective of this research work is to develop a scheme to detect and prevent the Sybil attack in the MANET and to provide a highly reliable data transmission approach. The proposed system ensures the availability, confidentiality, authenticity and reliability of the information using digital certificate chains and secret sharing schemes. To detect the sybil node during the route discovery process, the nodes authenticate each other by providing the digital security certificate (DSC). The digital security certificate proves the nodes and allows only authorized node to participate in the route to transmit the data packets from the source to destination. It will not ensure the confidential data transmission when the legitimate node exhibits the malicious behavior in certain circumstances. When any intermediate nodes learn about the data packet that is being transmitted, then the security in data transmission becomes a critical factor. The safety of the network can be enhanced by preventing the sybil attack in MANET by increasing the data confidentiality and reliability.  Only certified and authenticated nodes can participate in the route to transfer the data packets between the nodes. To prevent the sybil attack, it is necessary to secure the data that is transmitted over the insecure communication routes.